KAJIAN MORFOLOGIS DAN FISIOLOGIS KUDA (Equus caballus) LOKAL INDONESIA - , FIRDA FARIDA RAHMAH, Dr. drh. Yuriadi, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Population of Indonesia local horse has decreased annually by about 0.8% per year. Population decline is threatening the survival of Indonesia local horse, therefore conservation effort is needed. One of Indonesia local horse conservation efforts is identification of morphology and physiology data. The purpose of this study is to find out horseâs morphological data (height, body length, heart girth, and hips width) and physiology data (breathing frequency, pulse frequency and body temperature). In this study 45 horses were used, five horses were taken each from Batak horses, Minang horses, Priangan horses, Dieng or Kedu horses, Tengger horses, Lombok horses, Minahasa horses, Bima horses and Sumba horses. Method used is random sampling of local horses in every area of the horse name. The names of these areas have a tendency of horse population in Indonesia. Each of the horses was measured for its horseâs morphological data (height, body length, heart girth, and hips width) and physiology data (breathing frequency, pulse frequency and body temperature). The results showed that the morphology of Indonesia local horse can be classified as a pony. Physiology data of Indonesia local horse, includes pulse frequency, breathing frequency and body temperature, showed no differences with other horses.